The technological proposal based on enhanced recovery after cardiac surgery for changing traditional care in Latin America: REPLICCAR III Study Protocol - Gabrielle Barbosa Borgomoni; Pedro Horigoshi Reis; Guilherme Pinheiro; Fernando Faglioni Ribas; Gilmara Silveira da Silva; Valquíria Pelisser Campagnucci; Mário Issa; Pedro Silvio Farsky; Melina Moroz Barg; Marcos Gradim Tiveron; Luiz Fernando dos Reis Falcão; Roger Daglius Dias; et al. (PLoS ONE, 2025)
The length of hospital stay following cardiac surgery remains a significant challenge. Enhanced recovery protocols, alongside the use of health applications, offer promising potential for safely and effectively reducing postoperative length of stay. The Registro Paulista de Cirurgia Cardiovascular III (REPLICCAR III) study, registered at Clinicaltrials.gov (NCT06786819), aimed to investigate the impact of an optimization application integrated within an optimized recovery-based protocol on postoperative hospitalization duration in patients undergoing Coronary Artery Bypass Graft Surgery (CABG) in the state of São Paulo.